THE ROLE OF LOCAL CREDIT INSTITUTIONS (LPD) IN DISTRIBUTING AGRICULTURAL CREDIT IN PENATIH VILLAGE, DISTRICT OF EAST DENPASAR, DENPASAR CITY - ni Putu Era Prasistya Damayanti; I Nyoman Gede Ustriyana; AAA Wulandira Sawitri Djelantik (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2019)
Local credit institution (LPD) is financial enterprise that owned by the village to carry out business activities in that village and or the villagers. In its development, LPD has a imperative role that is not far from the goal of establishing LPD its sel, viz. Encouraging the development o rural economic throughraising the unds, distribute the loan for the community, create equal opportunities for business activities and employment opportunities for villagers.This study aims to determine characteristics of the agricultural debtor in LPD Desa Adat Penatih, the criteria for amount of agricultural credit distributed in LPD Desa Adat Penatih, the procedure for distributing agricultural credit in LPD Desa Adat Penatih and also the interference in repayment of credit in LPD Desa Adat Penatih. The location of this study were selected purposively. Data used in this study is qualitative data and quantitative data.The result of the study showed that the characteristics of the agricultural debtor in the LPD Desa Adat Penatih are seen from age and gender, the number of family dependents,  the level of education, the criteria for amount loan and the business fields. The amount of agricultural credit distributed in LPD Desa Adat Penatih base of the collateral value for collateral provided by debtor.  The procedure for distributing agricultural credit in LPD Desa Adat Penatih starts by of the loan application, analysis or assessment of credit, credit decision, disbursement and loan administration. There is no interference to LPD Desa Adat Penatih in repayment of agriculture credit. Both in terms of repayment period and credit collectibility.